Industrial buying behaviour process - Juhola, Laura (My University, 2008)
The past two decades have witnessed a fundamental change in the role of purchasing functions. The importance of purchasing has grown in several industries as a result of increasing specialisation, which also characterises the industrial system as a whole. Even though the importance of purchasing has now been recognised, in many companies the knowledge of purchasing function’s buying behaviour, its reasons and objectives and remains unclear. The main objective of this study is to describe, conceptualize and analyze the purchasing process of customized components within the case company. In addition to that, the different variables that encompass a number of supplier attributes that buyers assess in formulating their expectations regarding performance capabilities of potential component suppliers were researched. The theoretical framework of this study was based on the relevant previous academic research of this subject. The empirical research method is a single case study and several semi-structured interviews were carried out. In addition to that, a short survey of component supplier attributes was conducted. As a result of this study, a model of industrial buying behaviour process of customized components is presented. Also most important attributes of component supplier selection are introduced and analyzed. Some suggestions for further research are presented in the end of this study.
Keywords: Industrial buying; purchasing process; supplier selection; customized component; fi=Markkinointi|en=Marketing|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|